Dinamika Identitas Budaya dalam Era Globalisasi: Tantangan dan Kesempatan Media Sosial terhadap Budaya Masyarakat Lokal: Dynamics of Cultural Identity in the Era of Globalization: Challenges and Opportunities for Social Media on Local Community Culture - Fadilla Fahma; Desy Safitri; Sujarwo (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Globalization, especially through social media, has changed various aspects of cultural development significantly. These changes have triggered diverse dynamics and influenced culture at the local level. This process can be seen in the various phases of development that occur, with changes directly felt by local communities. Responses to globalization vary from avoidance, compromise, adaptation, to complete acceptance. As a result, challenges and opportunities arise in maintaining the cultural identity of local communities in the era of globalization.